The Arabidopsis NOT4A E3 ligase promotes PGR3 expression and regulates chloroplast translation - Bailey Mark; Ivanauskaite Aiste; Grimmer Julia; Akintewe Oluwatunmise; Payne Adrienne C.; Osborne Rory; Labandera Anne-Marie; Etherington Ross D.; Rantala Marjaana; Baginsky Sacha; Mulo Paula; Gibbs Daniel J. (Nature Research, 2022)
Chloroplast function requires the coordinated action of nuclear- and chloroplast-derived proteins, including several hundred nuclear-encoded pentatricopeptide repeat (PPR) proteins that regulate plastid mRNA metabolism. Despite their large number and importance, regulatory mechanisms controlling PPR expression are poorly understood. Here we show that the Arabidopsis NOT4A ubiquitin-ligase positively regulates the expression of PROTON GRADIENT REGULATION 3 (PGR3), a PPR protein required for translating several thylakoid-localised photosynthetic components and ribosome subunits within chloroplasts. Loss of NOT4A function leads to a strong depletion of cytochrome b6f and NAD(P)H dehydrogenase (NDH) complexes, as well as plastid 30 S ribosomes, which reduces mRNA translation and photosynthetic capacity, causing pale-yellow and slow-growth phenotypes. Quantitative transcriptome and proteome analysis of the not4a mutant reveal it lacks PGR3 expression, and that its molecular defects resemble those of a pgr3 mutant. Furthermore, we show that normal plastid function is restored to not4a through transgenic PGR3 expression. Our work identifies NOT4A as crucial for ensuring robust photosynthetic function during development and stress-response, through promoting PGR3 production and chloroplast translation.